Chapter A idade dos «desvios»: diacronia, variação social e linguística de corpus - Carvalheiro, Catarina (De Gruyter, 2016)
How and in which direction(s) is research in Ibero-Romance historical linguistics evolving? Now that the initial enthusiasm for the possibilities of digital corpora has worn off, the essays gathered in this volume reflect a more critical approach: corpora are being refined, while researchers discuss not only how reliable and representative they can be, but also ways in which to tackle certain gaps of the discipline.